Meningkatkan kemampuan sepak sila melalui metode latihan berpasangan pada permainan sepak takraw - Qadafi, Muammar Al; Kahar, Irsan; Ramli, Syamsul Alam; Jalil, Rasyidah (Jurnal Porkes, 2023)
This study aims to improve the learning outcomes of the skills of Silat in the game of sepak takraw for class VII students of MTs.AL-QASHASH TOBEA through the pair training method. Seeing that there are still many students who are less interested so that they are less serious in takraw learning activities, this causes the results of the ability of Sila Sila to not be optimal in the game of takraw. The data collection technique used in this study was the teacher's activity observation and student activity observation sheets as well as student skills tests. This research uses classroom action research (CAR). This research was conducted in 2 cycles and student evaluation tests were conducted at the end of each cycle. The results of the percentage of observations of student activity in the first cycle were the completeness of student learning outcomes in each cycle an average of 41.3% from the cognitive aspect, 58.6% from the affective aspect and 44.8% from the psychomotor aspect. in the first cycle and the second cycle of completeness of student learning outcomes in each cycle the average cognitive aspect is 93.1%, the affective aspect is 89.6% and the psychomotor aspect is 93.1%. The results of this study stated that the application of the pair training method could improve the learning outcomes of Sila Sila and was able to foster excitement and motivate students in learning.